Cell-free DNA predicts all-cause mortality of sepsis-induced acute kidney injury - Feixiang Xu; Xiao Tan; Jianli Wang; Su Lu; Hailin Ding; Mingming Xue; Yumei Chen; Sheng Wang; Jie Teng; Yiqin Shi; Zhenju Song (Renal Failure)
Background Sepsis-induced acute kidney injury (S-AKI) is a common complication in critically ill patients. Therefore, reliable biomarkers for predicting S-AKI outcomes are necessary. Serum cell-free DNA (cfDNA) is a circulating extracellular DNA fragment used as a noninvasive screening tool for many diseases, including sepsis. This study aimed to investigate the prognostic value of cfDNA in S-AKI patients and its relationship with some other parameters.Methods A total of 89 S-AKI patients admitted to the intensive care unit (ICU) from June 2021 to December 2021 were enrolled in this study. The patients were categorized into the low cfDNA group (< 855 ng/ml) and high cfDNA group (≥ 855 ng/ml) and were followed up for three months. CfDNA was extracted from serum and quantified using Quant-iT PicoGreen dsDNA Reagent.Results Overall survival was significantly lower in the high cfDNA group than in the low cfDNA group (Log-Rank p = 0.012). Univariate Cox proportional hazard model showed that cfDNA was significantly associated with all-cause mortality (HR [hazard ratio] 2.505, 95% CI [95% confidence interval] 1.184–5.298, p = 0.016). Also, serum cfDNA was a significant risk factor for all-cause mortality after adjusting for covariates (HR 2.191, 95% CI 1.017–4.721, p = 0.045). Moreover, cfDNA was positively correlated with several baseline parameters, including serum creatine, aspartate aminotransferase, alanine aminotransferase, prothrombin time, and International Normalized Ratio.Conclusion High serum cfDNA level is associated with higher mortality among the S-AKI population, indicating that cfDNA is a valuable biomarker for S-AKI prognosis.